The Projection of Digital Activism: The Dynamics of Digital Resistance Against Digital Authoritarian Repression In Indonesia - Muh. Asy'ari; Wan Nur Ain; Harni Indira (Department of International Relations, Hasanuddin University, 2026)
The shift of digital space from freedom to political control signals a new form of digital authoritarianism in Indonesia. The state uses online surveillance, information restrictions, disinformation, and activist criminalization to strengthen its power, coinciding with the decline of digital democracy in Southeast Asia. In contrast, hashtag-based resistance such as #ReformasiDikorupsi, #TolakOmnibusLaw, #IndonesiaGelap, and #ResetIndonesia has emerged, operating through connective action—horizontal mobilization based on personal networks and affective solidarity. This study employs descriptive qualitative methods, collecting data via library research and online observation during the #ResetIndonesia movement. Analyzed data included academic literature, international research reports, and credible media on digital surveillance and online social movements. The results show that connective action expands political participation by enabling digital creativity and spontaneous solidarity, but faces vulnerabilities due to the lack of formal organizations. Meanwhile, the state adapts repression through algorithms and regulations that normalize control. The dialectic of control and resistance forms a cycle—control, resistance, adaptation, new repression—that illustrates the co-evolution of power and digital activism. These findings stress the need to strengthen movement structures and protect digital rights to ensure online resistance evolves into a sustainable democratic force